Social isolation during pregnancy disrupts maternal behavior and hippocampal neurochemistry in rats: A role for BDNF, corticosterone, and GABAARα1 - Samira Khayat; Hamed Fanaei; Kiarash Anaraki Haji Bagheri (Comprehensive Psychoneuroendocrinology)
This study aimed to investigate the effects of social isolation stress during pregnancy on maternal behavior and associated neurochemical changes in the hippocampus of rats.Twenty female Sprague-Dawley rats were randomly assigned to either a group housing (two rats per cage: control group) or a social isolation stress group (one rat per cage: SI group) during pregnancy. At the end of the study, we assessed the levels of BDNF, corticosterone, and GABAARα1 in the hippocampus of the maternal brain, along with evaluating the endurance, integration, and emotional aspects of maternal behavior. Results indicated that social isolation stress significantly decreased maternal endurance, integration, and emotionality (self-calming) of maternal behavior. Concurrently, blood and the hippocampal corticosterone concentration significantly increased, while BDNF concentration significantly decreased in the SI stress group compared to controls. Moreover, GABAARα1 mRNA expression was significantly decreased in the hippocampus of socially isolated rats. These findings demonstrate that social isolation stress during pregnancy profoundly impacts maternal behaviors in rats, including endurance, integration, and self-soothing. The altered concentration of corticosterone and BDNF, and GABAARα1 mRNA expression in the hippocampus of social isolation group suggests disruptions in stress response regulation and synaptic plasticity during pregnancy to form normal maternal behavior.